2005
DOI: 10.1093/bja/aei057
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol as adjunct to psoas compartment block with levobupivacaine 0.5%: a randomized double-blinded study †

Abstract: We conclude that our data do not support a clinically important local anaesthetic or peripheral analgesic effect of tramadol as adjunct to PCB with levobupivacaine 0.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
(30 reference statements)
3
28
0
2
Order By: Relevance
“…They concluded results similar to our study [18]. (2010) found that mean sensory block time in dexamethasone and bupivacaine group was 1457 min [4,22]. The present study showed a significant prolongation of sensory analgesia with addition of dexamethasone 0.15 mg/kg as compared to tramadol addition which result in less prolongation of analgesia.…”
Section: Onset Of Motor and Sensory Blocksupporting
confidence: 90%
See 1 more Smart Citation
“…They concluded results similar to our study [18]. (2010) found that mean sensory block time in dexamethasone and bupivacaine group was 1457 min [4,22]. The present study showed a significant prolongation of sensory analgesia with addition of dexamethasone 0.15 mg/kg as compared to tramadol addition which result in less prolongation of analgesia.…”
Section: Onset Of Motor and Sensory Blocksupporting
confidence: 90%
“…Kapral S .et al (1999) added tramadol in total dose of 100 mg and S. Mannion et al (2004) used tramadol in dose of 1.5 mg/ kg as an adjunct [9,22].…”
Section: Resultsmentioning
confidence: 99%
“…Previous study in patients undergoing hip and knee arthroplasty showed that tramadol does not provide a clinically significant analgesic effect as an adjunct to 0.25% bupivacaine for continuous psoas compartment block [13]. It was reported that the use of systemic or perineural tramadol 1.5 mg /kg as adjunct to levobupivacaine psoas compartment block did not support a clinically important local anesthetic or peripheral analgesic effect [14].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed conflicting results about the efficacy of tramadol as adjuvant to local anesthetics some studies not prove it is efficiency [13][14][15] and others documented that it has a beneficial effect [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Há indícios também que possa modificar a transmissão dos impulsos de dor inibindo a recaptação de monoamina (Raffa et al, 1993 . Já na adição a bupivacaína para o bloqueio do músculo psoas não teve relação com alterações na duração do tempo de anestesia ou decréscimo na necessidade de analgésico pós-operatório (Mannion et al, 2005).…”
Section: Os Opióides Codeína Tramadol E Seus Isômerosunclassified